Contracts of Adhesion Between Law and Economics: Rethinking the Unconscionability Doctrine - D'Agostino, Elena (Springer, 2016)
This book examines the most controversial issues concerning the use of pre-drafted clauses in fine print, which are usually included in consumer contracts and presented to consumers on a take-it-or-leave-it basis.